The CCND1 c.870G>A polymorphism is a risk factor for t(11;14)(q13;q32) multiple myeloma - Weinhold, Niels; Johnson, David C.; Chubb, Daniel; Chen, Bowang; Försti, Asta; Hosking, Fay J.; Broderick, Peter; Ma, Yussanne P.; Dobbins, Sara E.; Hose, Dirk; Walker, Brian A.; Davies, Faith E.; et al. (Nature genetics, 2013)
Richard Houlston, Kari Hemminki and colleagues report a meta-analysis of genome-wide association studies of multiple myeloma and identify a variant in the CCDN1 gene that influences risk for developing a specific tumor karyotype with the t(11;14)(q13;q32) translocation.
Gesehen am 28.10.2021